Comportamento fotofísico do antraceno em sistemas micro-heterogêneos argila-surfactantes-íons metálicos - Magri, R. [UNESP]; Fertonani, F. L. [UNESP]; Pastre, I. A. [UNESP] (Ecletica Quimica, 2009)
Clays are a class of complex micro-heterogeneous and can be used as a substrate for adsorption. The sorption behavior of solid-phase enhanced by the presence of surfactants, organoclay, is an important phenomenon studied by environmental technology for removal of polycyclic aromatic hydrocarbons (PAHs) anthropogenic sources from water. This work aims to study the photophysical behavior of anthracene as a model of HPA systems in micro-heterogeneous clay-surfactant-metal ions (M (II) = Cd (II), Cu (II), Hg (II), Ni (II) and Pb (II); surfactants: CTACl; SDS; TR-X100). The experimental assays were conducted by monitoring changes in the static properties of fluorescence and anthracene emission suppression; anthracene was used as fluorescent probe. M(II)ions, like Cd(II), Cu(II), Hg(II), Ni(II) and Pb(II)were used as anthracene fluorescence suppressors. The profile of the fluorescence spectrum and the results of the suppression of fluorescence of the probe allowed inferring the specific place of the anthracene solubilization into the micro-heterogeneous systems studied and the consequent arrangement of them.
Photophysical behavior of anthracene in micro-heterogeneous systems clay-surfactant-metallic ions
Keywords: Anthracene; Clay; Fluorescence; Metallic ions; Suppression